“Senza andar nulla a pescare negli stranieri”: Jarro e il modello di Fortuné du Boigobey (Altre Modernità, 2019)
The article aims at rereading Giulio Piccini's (alias Jarro) literary works byidentifying the international models that underlie his production. Unduly defined as themysterious pioneer of Italian detective fiction, Piccini actually moulds his novels onGaboriau’s, Féval’s and especially Boisgobey’s production. La Vieillesse de MonsieurLecoq is presented as the main model for Piccini's most popular detective novel, I ladridi cadaveri: an actual repertoire of themes and sequences through which Piccini shapesthe first, serial detective novels in Italian literature.